STRATEGI MARKETING PUBLIC RELATIONS PT. TELKOM KANCATEL PATI DALAM PROGRAM “FLEXI DOOR TO DOOR” DAN “SPEEDY GO TO SCHOOL” UNTUK MEMBANGUN BRAND AWARENESS DAN BRAND KNOWLEDGE DI WILAYAH PATI - Atika Kurniasari; Puji Lestari; Isbandi Isbandi (Jurnal Ilmu Komunikasi, 2008)
Situation of urban community Pati which still jelling rural culture makes them has not so knowing is progress of communications technology which fanfare has the existing. PT. Telkom Kancatel Pati takes change of building awareness and knowledge of public about communica- tions technology by building brand awareness and brand knowledge product TELKOM in Pati region. This Skripsi entitle the “Strategy of Marketing Public Relations PT. Telkom Kancatel Pati in Program Flexi Door To Door and Speedy Go To School To Build the Brand Awareness and Brand Knowledge in Pati Region”. This research aim to know how strategy of Marketing Public Relations PT. Telkom Kancatel Pati in program “Flexi Door To Door” and “Speedy Go To School” to build the brand awareness and brand knowledge in Pati Region. Theory of Con- ditioning from Pavlov used for the based of depiction of activity of Marketing Public Relations and New Model Marketing as marketing base depicting unrighteous caring of producer to pay attention to the society importance as customer. Research type used by research having the character of qualitative with the descriptive study. Source used to collect the data was primary data that is with the direct perception or observation and secondary data that is literature or book studying about Marketing Public Relations, note or document PT. Telkom Kancatel Pati and other supporter data. Analyzed the this research data was analyzed entire all existing data from various source then make the ambit then compile the data to was then analyzed and in taking conclusion. Test the data validity by using source Triangulation. Result of research mentions that Flexi Door To Door is program Marketing Public Rela- tions PT. Telkom Kancatel Pati with strategy visits customer direct and offers product Flexi. Speedy Go To School is program Marketing Public Relations with strategy comes near customer though school community. Success of program Flexi Door To Door and Speedy Go To School in visible Pati region from many publics putting into use product Telkom Flexi and Telkom Speedy and product sales graph Telkom Flexi is increasing 80% until 85% and sales product Telkom Speedy increase until 87%. Media used at program Marketing Public Relations is banner, bro- chure, sponsorship, media print and electronic media. Cunclosion from this research is strategy Marketing Public Relations implemented by PT. Telkom Kancatel Pati in program Flexi Door To Door an Speedy Go To School successfully was implemented and obtains response which were positive from public.